Needle‐punched nonwoven matrix from regenerated collagen fiber for cartilage tissue engineering. Issue 13 (30th January 2014) - He, Nanfei; Ke, Qinfei; Huang, Chen; Yang, Jun; Guo, Yaping
ABSTRACT In this study, a new application of needle‐punched three‐dimensional (3D) fiber matrix from regenerated collagen fiber in articular cartilage tissue engineering (TE) was developed. Scanning electron microscopy images showed that the arrangement of fibers well mimicked the transitional part of the zonal articular cartilage. The 3D matrices exhibited a high porosity (93.5 ± 2.3%) and a large pore size range from about 20 μm in the inner part to 200–300 μm on the surface. The interconnected pore structure and hydrophilicity of the fibers led to the rapid and desired water uptake capacity of the matrices. Although the tensile and compressive properties of the scaffold were slightly lower than those of the natural articular cartilage, the anisotropic and nonlinear tension–compression were highly similar. In vitro human bone marrow stromal cells proliferation and cell morphology revealed the well cytocompatibility of the matrix, indicating its great potential in articular cartilage TE. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40404.